FREQUENCY OF INTRANASAL ADHESIONS IN SEPTOPLASTY WITHOUT NASAL SPLINTS IN CASES OF NASAL SEPTAL DEVIATION - Dr Muhammad mubbashir Afridi; Fazal Rehman; Hamza Nawaz khan; Adnan Khan; Muhammad Mustafa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Nasal septal deviations play a critical role in nasal obstruction symptoms, aesthetic appearance of the nose, increased nasal resistance, and sometimes snoring. The purpose of this study is to determine the frequency of intranasal adhesions in septoplasty without nasal splints in cases of nasal septal deviation.Methods: Present study was descriptive case series availed from the ENT department of Hayatabad Medical Complex, Peshawar. The study duration was six months, from February, 2021 until August, 2021. The data was collected via non-probability consecutive sampling method. All patients were operated under general anesthesia & without nasal splints but with simple nasal packing using vaseline gauze packs under the supervision of ENT consultant having at least seven years post fellowship experience.Results: Mean age of the patients included in the study was 30.52 ± 6.67 years. Mean duration of the disease was 4.84 ± 2.3 months. In the age range of 15-30 years, 3.3% reported nasal adhesion, while based on gender 3.2% male patients were observed with nasal adhesion. Similarly, based on operative times, no patient reported nasal adhesion < 45 minutes operation time. None of the findings were found statistically significant.Conclusion: Our study demonstrates that silastic splints cannot prevent intranasal adhesions in case of septoplasty. Furthermore, removal of silastic splints will be painful in such patients.